2020
DOI: 10.1002/cplu.202000319
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Reactive Gases: A Tale of Taming Carbon Monoxide

Abstract: This Personal Account describes the development of air‐stable and solid precursors for on‐demand release of carbon monoxide. In combination with the development of a two‐chamber reactor, COware®, CO liberation can be achieved under safe working conditions, as well as allowing transition metal‐mediated carbonylations with stoichiometric carbon monoxide. Particularly appealing is the adaptability of this chemical technology for the preparation of carbon isotope labeled bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“… 28 The reaction was run in a two-chamber system, where one chamber is dedicated to the in situ production of carbon monoxide from Mo(CO) 6 , which can then diffuse to the other chamber where the carbon monoxide-consuming benzyloxycarbonylation can occur. 29 , 30 Employing these conditions, the C- and N-protected unnatural amino acid 10 was synthesized and isolated in 64% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 The reaction was run in a two-chamber system, where one chamber is dedicated to the in situ production of carbon monoxide from Mo(CO) 6 , which can then diffuse to the other chamber where the carbon monoxide-consuming benzyloxycarbonylation can occur. 29 , 30 Employing these conditions, the C- and N-protected unnatural amino acid 10 was synthesized and isolated in 64% yield.…”
Section: Resultsmentioning
confidence: 99%
“…In order to access the benzyl-protected C-terminal end of our desired unnatural amino acid, aryl bromide 9k was subjected to a palladium-catalyzed benzyloxycarbonylation with a PdOAc 2 :XantPhos catalytic system (Scheme ). The reaction was run in a two-chamber system, where one chamber is dedicated to the in situ production of carbon monoxide from Mo­(CO) 6 , which can then diffuse to the other chamber where the carbon monoxide-consuming benzyloxycarbonylation can occur. , Employing these conditions, the C- and N-protected unnatural amino acid 10 was synthesized and isolated in 64% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has a longstanding interest in enabling the use of small gaseous molecules by stoichiometric ex situ release of gaseous reagents from easy-to-handle precursors in two- or three-chamber reactors. We have reported the utilization of hydrogen, , carbon monoxide, ethylene, methanethiol, and hydrogen cyanide in this manner, establishing the application of specialized gas precursors for chemical synthesis and isotope labeling. De Borggraeve et al have also demonstrated the utility of the two-chamber reactor for sulfuryl fluoride generation .…”
Section: Introductionmentioning
confidence: 99%
“…CO donors are safer alternatives and have potential for drug development . A plethora of CO-releasing molecules have been reported, including carbonyl–metal complexes and triggered CO donors . Recently, Choi et al reported neuroprotective effects of CO during I/R …”
mentioning
confidence: 99%